Genome-wide analysis of UDP-glycosyltransferases family and identification of UGT genes involved in drought stress of Platycodon grandiflorus - Chen, Bowen; Wang, Xinrui; Yu, Hanwen; Dong, Nan; Li, Jing; Chang, Xiangwei; Wang, Jutao; Jiang, Chao; Liu, Juan; Chi, Xiulian; Zha, Liangping; Gui, Shuangying (Frontiers in Plant Science, 2024)
The uridine diphosphate (UDP)-glycosyltransferase (UGT) family is the largest glycosyltransferase family and is involved in abiotic stress. Although UGT has been studied in many medicinal plants, there are few reports on Platycodon grandiflorus.Here, a total of 75 UGT genes (PgUGTs) were identified in P. grandiflorus genome and clustered into 14 subgroups. The PgUGTs were distributed on nine chromosomes, containing multiple cis-acting elements and 22 pairs of duplicate genes were identified. Protein-protein interaction analysis was performed to predict the interaction between PgUGT proteins. Additionally, six genes were upregulated after 3d under drought stress and three genes (PGrchr09G0563, PGrchr06G0523, PGrchr06G1266) responded significantly to drought stress, as confirmed by qRT-PCR. This was especially true for PGrchr06G1266, the expression of which increased 16.21-fold after 3d of treatment. We cloned and conducted bioinformatics analysis of 2 three candidate genes, both of which contained conserved motifs and several cis-acting elements related to stress response, PGrchr06G1266 contained the most elements. To summarize, this study identified three genes that highly respond to drought stress, laying the foundation to better understand the molecular bases of responses to drought stress and the biosynthesis of platycodin.